Вяжущие вещества, бетоны и изделия из них: учебное пособие для вузов - Горчаков Г. И. Григорий Иванович; Хигерович М. И. Моисей Исаевич; Иванов О. М. Орест Михайлович; Домокеев А. Г. Александр Георгиевич; Ерофеева Е. А. Екатерина Алексеевна; Орентлихер Л. П. Лидия Петровна (Москва, Высшая школа, 1976)
Авт. указ. на обороте тит. л.